Strategi Percepatan Pertumbuhan dan Transformasi Struktural Kabupaten dan Kota (Studi Kasus Provinsi Nusa Tenggara Barat) - Andi Pramaria (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
District and City Development in West Nusa Tenggara Province faces problems regarding the economic structure that still relies on the primary and tertiary sectors; economic growth that tends to decline (2015-2020); inequality between regions and the intervention of the West Nusa Tenggara Provincial government which has not shown the types and locations of activities as stated in the RPJMD. The research objectives are (1) to determine the position of each sector; (2) analyze the disparity between regions; and (3) formulating the design of intervention strategies for growth and structural transformation. The analytical tools used are (1) Location Quotion (LQ) to determine the basic and non-basic sectors, (2) Shift Share (SS) to determine growth and transformation, (3) Overlay technique, to determine sector position, (4) Williamson Index to determine the inequality between regions, (5) Klassen typology to determine the position between regions, and (6) RPJMD analysis to determine the economic strategy in growth and structural transformation. The results of the study show (1) although regional economic growth tends to decline, there are still some sectors that are able to grow positively and have advantages; (2) Districts and Cities in West Nusa Tenggara Province are devided in the category of prosperous regions, prosperous in the process of declining and lagging behind in the development process, (3) intervention strategies for accelerating growth and structural transformation are carried out through (a) Agriculture and Investment development; (b) Development of Reliable Tourism, and (c) development of Superior Industry